2015
DOI: 10.1117/12.2075719
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Varioptic's liquid lens based on electrowetting: how to obtain a short response time and its application in the design of a high resolution iris biometric system

Abstract: a Varioptic, a Business Unit of Parrot S.A., 24 B rue Jean Baldassini, 69007 Lyon (France); b Département d'optique théorique et appliquée, Unité haute résolution angulaire, ONERA, 29 AvABSTRACT This communication presents the results obtained for decreasing the response time of electrowetting-based real time focus correctors (liquid lenses).In order to provide a compact iris biometric system demonstrator, we have achieved a response time at 90% of 7.5 ms for a change in focalization from 0 diopter to 10 diopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…We demonstrated more complex 3D scans with tilted field imaging, which may be important for accessing features that are not confined to a single focal plane. In this study we altered the EWTL FL slowly through the scan, but the EWTL has been shown to be capable of varying the FL at ~50 Hz or greater when driven at resonance 37 , 38 . In the future we can implement more efficient driving functions for the EWTL to achieve high-speed axial scanning, opening the potential for random-access scanning for truly volumetric data collection 3 , 4 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated more complex 3D scans with tilted field imaging, which may be important for accessing features that are not confined to a single focal plane. In this study we altered the EWTL FL slowly through the scan, but the EWTL has been shown to be capable of varying the FL at ~50 Hz or greater when driven at resonance 37 , 38 . In the future we can implement more efficient driving functions for the EWTL to achieve high-speed axial scanning, opening the potential for random-access scanning for truly volumetric data collection 3 , 4 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated more complex 3D scans with tilted field imaging, which may be important for accessing features that are not confined to a single focal plane. In this study we altered the EWTL FL slowly through the scan, but the EWTL has been shown to be capable of varying the FL ∼50 Hz or greater when driven at resonance 37,38 . In the future we can implement more efficient driving functions for the EWTL to achieve high-speed axial scanning, opening the potential for random-access scanning for truly volumetric data collection 3,4,39 .…”
Section: Discussionmentioning
confidence: 99%
“…The low liquid viscosity and interfacial tension can reduce the response time of the lens. [67] In addition, Supekar et al studied the relationship between the response time and the input voltage and obtained the best shape of driving voltage with the fastest response time. It was shown that the response time was decreased by 29% with two exponential input voltages.…”
Section: Liquid Lens With Single Liquid-liquid Interfacementioning
confidence: 99%